Emotional Intelligence, Subjective Wellbeing, and Work-Family Conflict Among University Lecturers - Amalia Juniarly; Ayu Purnamasari; Dewi Anggraini; Heni Andini (ANIMA Indonesian Psychological Journal, 2019)
The purpose of this study is to determine the role of emotional intelligence and subjective wellbeing in predicting work-family conflict. The participants for the study were 182 female lecturers at University of Sriwijaya, and the pilot study of the measuring scales was conducted with 52 lecturers. The scales used were the scales of emotional intelligence, subjective well-being and work-family conflict. Data analysis employed multiple linear regression. The results of the analysis were that there is a significant role for emotional wellbeing and subjective wellbeing concerning work-family conflict.